BOILER INSPECTION PLANNING CFB THERMAL POWER PLANT BASED ON CONDITION PERFORMANCE OF BOILER CASE STUDY PULANG PISAU THERMAL POWER PLANT ii 2X60 MW - Subekti Muslim Saputra, Ahmad
Planning boiler inspections especially for the CFB type power plant currently does not have a standard standard. The advantage of this study is to provide a new alternative to inspection planning with reference to boiler performance conditions. The method is done by collecting boiler performance data that is measured routinely and correlates with the operating hours of the plant. The data taken are pipe thickness, boiler efficiency and sealpot temperatur. The data is processed using exsisting standard as API 570 Standard for calculating pipe corrosion rates, API 510 and ASME BPVC standards for calculating remaining service life of pipes, regression analysis to predict inspection hour recommendations, and modeling using Weibull and MonteCarlo distributions to calculate availability and risk of RCFA program improvement results for boiler areas.